Accuracy of 3D Printed Casts from Digital Implant Scans versus Stone Casts from Conventional Impressions: A Comparative Study in the Anterior Maxilla - Banjar, Ayman. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Posthodontics.; Advisor: Panos Papaspyridakos.; Committee: Yo-wei Chen, Aikaterini Kostagianni, Matthew Finkelman, and Aikaterini Papathanasiou.; Keyword: Dentistry.